Retinal digest preparation: a method to study diabetic retinopathy - Dietrich, Nadine; Hammes, Hans-Peter (Animal Models in Diabetes Research, 2012)
Retinal digestion is a commonly used method for studying experimental diabetic retinopathy in animal models. The method allows to assess qualitatively and quantitatively the morphology of the retinal vasculature, including characteristics of endothelial cells and pericytes. The digestion method uses the enzyme trypsin and enables the precise evaluation of venolar and arteriolar diameters, endothelial cell and pericyte numbers, and the formation of acellular capillaries.
Gesehen am 13.02.2019